Pengaruh Burnoutdan Self Efficacy Terhadap Organizational Citizenship Behavior dan Kinerja Karyawan pada PT. Kelapa Sawit Kabupaten Sambas Kalimantan Barat - Suci Harira Sari Hatuina; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
High self-efficacy will achieve better performance because the individual has strong motivation, clear goals, stable emotions and the ability to perform activities or behavior successfully. Self-efficacy reflects an individual's belief in his or her ability to carry out a task at a specific level of performance. Self-efficacy is a belief that arises from having self-confidence in one's ability to carry it out. This research aims to examine the influence of burnout and self-efficacy on Organizational Citizenship Behavior and employee performance at PT. Sambas Regency Oil Palm, West Kalimantan. Data collection in this research was carried out using a questionnaire which was answered directly by the respondents via a Google Form link. Questionnaires that have been completed by respondents will automatically be seen on the link for filling in the respondent's questionnaire which will then be tabulated in Microsoft Office Excel 2007 and processed using the SPSS program.